Analysis of People Response on Twitter Towards Tidal Wave Disaster in the Southern Coast of Yogyakarta Special Province (Case Studies: Parangtritis Beach, Bantul Regency) - Indratmoko, Satria; Al Hakim, Inayah Bastin; Satrio Guntoro, Wahyu (KnE Social Sciences, 2019)
In July 2018 the movement of the wind from Australia to the Indian Ocean gives the impact on season transition from rainy to dry season. As the result, the wave becomes so much higher than normal condition as it hits the coastal area as well as in the southern part of Yogyakarta Special Province where is directly bordered with the Indian Ocean. Some impacted areas are popular tourism spots like Parangtritis Beach. The wave wrecks several shops along the beach owned by the local people. The majority of damaged objects are semi-permanent buildings constructed by traditional bamboo and timber. Moreover the tourism activity has been warned due to the dangerous condition. The advancement of technology becomes one of popular issues including the increasing of online social media usage. Internet and gadgets such as smartphone are recently the part of people lifestyle. The nowadays people prefer to access anything online through their smartphone including to find the news on the website or social media such as Twitter. One of interested news is about disaster particularly in recognizable places as well as about tidal wave disaster in Parangtritis Beach. This study aims to investigate the advantages of Twitter contents related to the tidal wave in Parangtritis Beach on people response about the disaster and the beach. The analysis applies sentiment analysis theory. Furthermore the data being collected in this research is online from Twitter accounts that has divided into three phases of disaster (before tidal wave, during tidal wave, and after tidal wave). Keywords: Twitter, Tidal Wave, Sentiment Analysis